PENINGKATAN MINAT BACA KARYA SASTRA CERPEN MELALUI PENDEKATAN SINEKTIK PADA SISWA KELAS VI - Sari, Apri Kartika (Premiere Educandum, 2014)
At the elementary school level, teaching literature is still experiencing growth phase is quite difficult. Among difficulties faced by the teachers one of which is the lack of student interest in reading short stories to literature. Under these conditions, the purpose of this research is to increase interest in reading literary short story in the sixth grade students of SDN 02 Dawu District Paron, Ngawi. The subjects were 24 sixth grade students at SDN 02 Dawu studied using observation techniques. The results of the studies that have been done two cycles are known to increase in reading scores of students were assessed four aspects, namely the aspect of personal consciousness, volition, attention, and aspects of the feelings of pleasure. This study concludes that the approach sinektic the students interest at the rate of two cycles of 62.45 while still using the conventional approach, the numbers increased to 83.49 when students have experienced learning approach to rate hikes sinektic reading the sixth grade students of SDN Dawu 02 at 21.04.Keywords: Interest in reading, short stories, approaches sinektic